Tinjauan Literatur: Pertimbangan Klinis Antiinflamasi Nonsteroid selama Kehamilan Berdasarkan Profil Risiko dan Keuntungan Terapeutik - Kemuning Pancar Wangi; Cut Nadia Anne Sanha; Noor Cahaya (Aesculapius Medical Journal, 2026)
Abstract [Literature Review: Clinical Consideration for Nonsteroidal Antiinflammatory Drugs in Pregnancy Based on Risk Profile and Therapeutic Benefits] The use of nonsteroidal anti-inflammatory drugs (NSAIDs) in pregnant women is an important topic in clinical practice, given the potential risks to both the mother and the fetus. NSAIDs are commonly used to treat pain, inflammation, and fever, but their use during pregnancy should be approached with caution due to evidence linking them to various complications. This study aimed to evaluate the impact of NSAIDs administration based on the type of drug, trimester of exposure, and maternal clinical condition, thus influencing NSAIDs therapy in pregnant women. The method used in this study was a literature review using PubMed and Google Scholar databases, resulting in five articles selected through inclusion and exclusion. Nonselective NSAIDs such as ibuprofen, naproxen, ketoprofen, and indomethacin are associated with an increased risk of prematurity, major congenital malformations, and oligohydramnios, especially when used in the first trimester or long-term. Given these risks, the use of NSAIDs during pregnancy requires careful consideration. In contrast, low-dose aspirin has been shown to have protective benefits in preventing pregnancy complications such as preeclampsia and preterm birth in high-risk pregnancies, particularly when initiated in the first trimester. Based on evidence from cohort studies and randomized controlled clinical trials, NSAIDs use during pregnancy should be selective, considering the type, dose, and timing of administration, and should be closely monitored by a healthcare professional. Keywords: NSAIDs, pregnancy, trimester, prematurity, preeclampsia